Comparison of capillary blood ketone measurement by electrochemical method and urinary ketone in treatment of diabetic ketosis and ketoacidosis in children - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (SPRINGER, 2008)
We aimed to compare the recent practical method of capillary beta-hydroxy butyrate (beta OHB) measurement with the widely used urinary ketone measurement in monitoring metabolic status of the patient during treatment of diabetic ketoacidosis (DKA) and diabetic ketosis (DK). Patients with DKA and DK admitted to the hospital were followed with simultaneous measurements of capillary beta OHB by electrochemical method (Medisense Optium, Abbott), and urinary ketone by semi-quantitative method. Blood gases were measured in 2-4 h intervals. Fourteen patients with DKA/DK (7 males and 7 females, age: 9.2 +/- 4.2 years) were included with 50 simultaneous measurements of capillary and urinary ketone. No correlation was detected between urinary ketone and blood pH (P = 0.06) and HCO(3) (P = 0.79), whereas a significant negative correlation was found between capillary beta OHB and blood pH (r = -0.41, P < 0.05) and HCO(3) (r = -0.35, P < 0.05). Capillary beta OHB and urinary ketone levels did not correlate at the beginning and 3.3 +/- 1.4 h after treatment, but did correlate in the third samples taken 7.8 +/- 2.0 h after treatment (r = 0.8, P < 0.05). Capillary beta OHB levels show good correlation with the degree of acidosis (pH and HCO(3)). Capillary beta OHB measurement is more sensitive than urinary ketone measurement in reflecting the patient's metabolic status and improvement during treatment.
Keywords: diabetic ketoacidosis; type 1 diabetes mellitus; beta-hydroxy butyrate; urinary ketone; ketone measurement; 3-HYDROXYBUTYRATE; MANAGEMENT